1993
DOI: 10.1172/jci116547
|View full text |Cite
|
Sign up to set email alerts
|

Expression of 92-kD type IV collagenase/gelatinase (gelatinase B) in osteoarthritic cartilage and its induction in normal human articular cartilage by interleukin 1.

Abstract: We report here that a 92-kD gelatinolytic metalloproteinase is expressed as protein and mRNA in human osteoarthritic cartilage, but not in normal adult articular cartilage. Western immunoblotting demonstrated that the 92-kD gelatinolytic activity corresponded to 92-kD type IV collagenase/gelatinase (gelatinase B); mRNA for gelatinase B was identified by Northern blotting. Chondrocytes from normal cartilage also exhibited mRNA for 72-kD type IV collagenase/gelatinase (gelatinase A), tissue collagenase, and stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
89
0
5

Year Published

1995
1995
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(103 citation statements)
references
References 48 publications
(30 reference statements)
4
89
0
5
Order By: Relevance
“…The enzyme has been isolated and characterized from a number of different cell types [1][2][3]. Tt~e expression of MMP-9 is implicated to both physiological an.t pathological breakdown of the connective tissue during invasion of cytotrophoblasts [4], the detachment of epithelial cells from basement membrane in the wound healing process [5 chronic inflammation such as rheumatoid arthritis [6,7] and tumor cell invasion and metastasis [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The enzyme has been isolated and characterized from a number of different cell types [1][2][3]. Tt~e expression of MMP-9 is implicated to both physiological an.t pathological breakdown of the connective tissue during invasion of cytotrophoblasts [4], the detachment of epithelial cells from basement membrane in the wound healing process [5 chronic inflammation such as rheumatoid arthritis [6,7] and tumor cell invasion and metastasis [8].…”
Section: Introductionmentioning
confidence: 99%
“…Fhe synthesis of proMMP-9 has been shown to be regulated by 12-O-tetradecanoylphorbol 13-acetate (TPA), interle~ kin 1 (IL-I), tumor necrosis factor a (TNFa) and transfo~'ming growth factor 131 in various cell lines [1,[5][6][7][8]. H ~wever, little evidence has been provided for the combined el~ act of those cytokines on the production of proMMP-9.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, MMP-1 (interstitial collagenase, EC 3.4.24.7), which specifically degrades native types I, II and III collagen [3], and MMP-3 (stromelysin 1, EC 3.4.24.17), which digests proteoglycans and collagen types IX and X [4][5][6][7][8], are probably key enzymes involved in the pathological destruction of cartilage. In addition to these two enzymes it has been suggested that MMP-9 (gelatinase B, EC 3.4.24.35) plays a role in the degradation of cartilage since it is expressed in osteoarthritic cartilage [9] and is able to degrade proteoglycans [10].…”
Section: Introductionmentioning
confidence: 99%
“…MMP-3 normally is not expressed to an appreciable extent, but it is induced by cytokines, including IL-1 and TNFa [Nagase and Woessner, 1999]. Expression of MMP-9 (92 kD gelatinase) in joint cartilage from patients with osteoarthritis suggests that MMP-9 is involved in progressive articular cartilage degradation in these patients [Mohtai et al, 1993], and elevated serum levels of MMP-9 are associated with a high risk for coronary artery events [Ferroni et al, 2003]. MMP-1 is detected in synovium shortly after onset of symptoms in patients with inflammatory arthritis [Cunnane et al, 1999], and it is abundant at the bone-implant interface of failed prosthetic joints [Pap et al, 1999].…”
mentioning
confidence: 99%